Peningkatan Kompetensi Musik Jemaat melalui Pelatihan Suling Bambu Berbasis Sistem Nada - Nelsano Anesry Latupeirissa; Novan T Salamena (Pakis Journal Institute, 2026)
This community service activity aims to enhance congregational musical competence through training in the construction and performance of bamboo flutes based on a tonal system in Maneoratu Village, Central Maluku. The activity is motivated by the predominance of intuitive practices in making and using bamboo flutes without standardized tuning, which limits musical development in worship contexts. The method employed is a qualitative participatory approach through hands-on training involving participants in instrument construction, playing techniques, and basic accompaniment skills for congregational music. The results indicate an improvement in participants’ understanding of tonal systems, skills in constructing and playing bamboo flutes, as well as increased participation and social interaction within the community. Furthermore, the activity contributes to transforming musical practices from intuitive traditions toward more systematic and structured approaches. Therefore, this training provides not only technical benefits but also contributes to cultural strengthening and the enhancement of congregational musical quality.